Effect of deposition strategies on mechanical strength of wire arc additively manufactured Inconel 625. (2022) - Singh Rajput, Gautam; Gor, Meet; Soni, Harsh; Badheka, Vishvesh; Sahlot, Pankaj
Abstract: Wire arc additive manufacturing (WAAM) is a cutting-edge technique for fabricating complex three-dimensional structures. Due to the high thermal gradient and phase transition in the WAAM process, fabricating defect-free structures with good mechanical properties is challenging. As a result, studying the WAAM process is critical for producing 3D components with low residual stress and high strength. In this paper, GMAW based WAAM is used with three alternative modes of deposition strategies to fabricate the structure of Inconel 625. The temperature variation during deposition of layers, macroscopic analysis, flatness deviation and strength of the deposited structure is investigated. The temperature distribution demonstrates that as the number of deposited layers increases, the fluctuation in peak temperature at the substrate decreases. In all modes, macroscopic examination showed defect-free bonds between Inconel 625 deposited layers. The minimum flatness deviation of 0.38 mm has been found in mode-1 (deposition from one side). However, the maximum ultimate tensile strength (UTS) of 796 MPa achieved in Mode-3 (deposition with pre-heated substrate). The pre-heating of substrate results in improved strength of fabricated components due to reduction in thermal cycle. The pre-heating of substrate is one of the most effective methods for fabricating Inconel 625 structure with high strength. This research will aid in improving the mechanical properties of WAAM fabricated structures.